Characterizing Basic and Complex Usage of i2b2 at an Academic Medical Center - Sholle, Evan T. (AMIA Jt Summits Transl Sci Proc, 2020)
Developed to enable basic queries for cohort discovery, i2b2 has evolved to support complex queries. Little is known whether query sophistication – and the informatics resources required to support it – addresses researcher needs. In three years at our institution, 609 researchers ran 6,662 queries and requested re-identification of 80 patient cohorts to support specific studies. After characterizing all queries as “basic” or “complex” with respect to use of sophisticated query features, we found that the majority of all queries, and the majority of queries resulting in a request for cohort re-identification, did not use complex i2b2 features. Data domains that required extensive effort to implement saw relatively little use compared to common domains (e.g., diagnoses). These findings suggest that efforts to ensure the performance of basic queries using common data domains may better serve the needs of the research community than efforts to integrate novel domains or introduce complex new features.